The traditional economic systems based on local wisdom of indigenous communities in Indonesia - Wazin, Wazin; Mahfud, Mahfud (International Journal of Nusantara Islam, 2025)
This study aims to explore the traditional economic systems of indigenous communities in Indonesia, focusing on the roles of local wisdom and cultural practices in sustaining livelihoods. The research examines Banten, West Java, Central Java, and Bali indigenous communities to understand how their economic systems integrate sustainability and cultural preservation. The study employs a qualitative ethnographic research design. Data were collected through participant observation, in-depth interviews, and documentation within the respective communities. Fieldwork focused on agricultural practices, economic distribution patterns, and the integration of cultural norms in economic activities. The findings reveal that the Kasepuhan communities in Banten and West Java practice sustainable rice farming under the guidance of traditional leaders, adhering to once-a-year planting to maintain soil fertility. In Bali, the Tri Hita Karana philosophy underpins the Subak irrigation system, ensuring harmony between agriculture, nature, and spirituality. The Samin community in Central Java demonstrates resilience through crop diversity and equitable resource distribution, prioritizing communal welfare and ecological balance. This study contributes original insights into the intersection of traditional knowledge and economic sustainability, addressing gaps in previous research that have often overlooked economic practices. It highlights Indigenous economic systems' adaptability and potential to inform sustainable development strategies.